1982
DOI: 10.1093/nar/10.8.2625
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of high efficiency promoter sequences inSaccharomyces cerevisiae

Abstract: The position of the yeast phosphoglycerate kinase (PGK) gene has been mapped on a 2.95kb Hind III fragment. We have determined the nucleotide sequence of the 5' flanking region and compared this sequence with those from 16 other yeast genes. PGK, like all other yeast genes has an adenine residue at position -3. It has two possible TATA boxes at positions -114 and -152 and a CAAT box at -129. In addition we have defined a structure at position -68 to -39 that is common to all yeast genes that encode an abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
189
2
3

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(205 citation statements)
references
References 37 publications
11
189
2
3
Order By: Relevance
“…Immediately before the proposed AR01 translation start is an A at the third position before the ATG codon. An A at this position is invariant amongst S. cerevisiae genes [20]. The location of the transcription start site (5'-end of the message) in the DNA sequence was determined by the detection of primer extensions with reverse transcriptase on S. cerevisiae mRNA, and confirmed by detection of DNA/RNA hybrids protected from digestion by nuclease $1 (not shown).…”
Section: Dna Sequence Analysis Of Aro1mentioning
confidence: 99%
“…Immediately before the proposed AR01 translation start is an A at the third position before the ATG codon. An A at this position is invariant amongst S. cerevisiae genes [20]. The location of the transcription start site (5'-end of the message) in the DNA sequence was determined by the detection of primer extensions with reverse transcriptase on S. cerevisiae mRNA, and confirmed by detection of DNA/RNA hybrids protected from digestion by nuclease $1 (not shown).…”
Section: Dna Sequence Analysis Of Aro1mentioning
confidence: 99%
“…The sequence TAAATAA is found in tandem repeat at locations -141 and -134, and is followed by the sequence AT repeated six times. A number of yeast genes that encode abundant mRNAs seem to have their transcription start sites at or very near the sequence CAAG and a CT rich block is usually found upstream of the CAAG sequence (32,39,40). In the RAD3 gene, there is no CT rich block nor a CAAG sequence in the vicinity of the mRNA start site.…”
Section: Sequence Of the Rad3 Gene And Proteinmentioning
confidence: 99%
“…It has been suggested that efficient initiation of translation in eukaryotes depends on a purine residue, usually an A, at position -3 relative to the initiating ATG codon (40,41). The -3 position ofthe RAD3 gene is occupied by an A residue.…”
Section: Sequence Of the Rad3 Gene And Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…From the data summarized in table 2 it is obvious that_ in several cases the capping region can be extended to the sequence AACCAAG found near the 5 '-end of the mRNAs. The untranslated 5 ' -terminal part of the L16 mRNA contains the sequence CATACA, implicated in control of translation efficiency [23] and shows the prefered environment for the initiation codon [27]. Upstream from the 5'-end of the L16 gene the TATA-like structure [28] TAATATTAT is present at position -62.…”
Section: Resultsmentioning
confidence: 99%